The continuous postoperative peritoneal lavage diffuse peritonitis in acute: preliminary communication - Carriquiry, Luis; Cazabán, Luis A; Baldizán, Jorge W (Cirugía del Uruguay, 1976)
ntinuous postoperative peritoneal lavage may help to reduce that rate. According to severa! experimental data, it is based upon the convenience of removing by mechanical means the maximum possible bacterial population from the peritoneum in order to make an effective local defense easier. Based upon their still short experienc-e, the authors point out the principal points in the_ techniques of performance ( care:f ul placing of the infusion and drainage tube-s, us-e of a lavage solution with antibiotics in Jarge quantíties and wit.h continuous infusion) and of control (bacteriological, hydroelectrolitical, and of volume). They also analize the principal mishaps ( obstruction of the drainage tubes, appearence of intraperitoneal liquid shortcircuits, loss of liquid through parietal fissures), and som-e accidents ( superhydration, potasic and proteic depletion) which may occur during the performance of the technique.